(untitled) (International Journal of Engineering and Computer Science, 2015)
Cryptography is the one of the main categories of computer security that converts information from its normal form into an unreadable form. The two main characteristics that identify and differentiate one encryption algorithm from another are its ability to secure the protected data against attacks and its speed and efficiency in doing so [9]. The process of encoding plaintext message into cipher text messages is called as encryption. The reverse process of transforming cipher text message back to plaintext message is called as decryption.[3] This paper provides the comparison between three symmetric key cryptographic techniques namely as DES, AES and Blowfish algorithms in terms of time and security by using image simulation. The tool used for the present work is NetBeans IDE 7.4. It observed that Blowfish algorithms took least time for simulation of encryption and decryption.